Effect of Grinding Environments on Magnetic Response of AISI D2 Tool Steel - Sharma A.; Chaudhari A.; Awale A.S.; Yusufzai M.Z.K.; Vashista M. (My University, 2025)
Abstract: Nowadays, precision manufacturing industries are required faster surface inspection tools for the achievement of high productivity. In this context, the Barkhausen noise (BN) technique is adopted as a quick response technique in the grinding for qualitative evaluation of surface integrity of AISI D2 tool steel. Present work investigates the effect of eco-friendly coolant, i.e., cryogenic, on surface integrity of ground sample in the plunge grinding mode at different downfeed and compared with dry and wet environments. Surface integrity was assessed in respect of surface roughness, microstructure, and microhardness. Magnetic response of ground surface was reported by Barkhausen noise analyzer in the form of root mean square (rms), peak, and number of pulses. From the outcomes, it was perceived that no significant variations were found in the microstructure and microhardness of the ground surface and subsurface after cryo-grinding owing to lower thermo-mechanical loading. Besides, lower surface roughness was obtained in the case of cryo-grinding because of thermal softening effect. A linear correlation between BN input parameters, i.e., magnetic field intensity and BN responses at different magnetizing frequency could be achieved. Finally, better BN responses, including higher rms, peak, and number of pulses, were found under the cryogenic environment. © 2021, Pleiades Publishing, Ltd.